(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Streptococcus agalacticae is a pathogen associated with maternal and neonatal morbidity and mortality. The current gold standard for preventing neonatal sepsis is the intrapartum antibiotic prophylaxis (IAP) of Streptococcus agalacticae-positive mothers. Antimicrobial resistance is on the rise and increasingly threatens public health. Therefore, the responsible use of antibiotics is critical. Switzerland lacks unified IAP guidelines. IAP management varies by obstetric ward and is based on various national and international guidelines. This study aimed to gain an overview of the variability of existing internal protocols for IAP for Streptococcus agalacticae in Swiss obstetrics wards. METHOD: In March and April 2024, all identified obstetric wards in Switzerland were contacted and invited to submit their internal protocols so that they could be analysed for the choice of antibiotics for IAP, the referenced literature supporting their protocols and the professions involved in their development. RESULTS: Of 87 departments contacted, 43 (49%) shared their protocols. Three β-lactam antibiotics were identified as the first choice: penicillin G (56%, n = 24), amoxicillin (28%, n = 12) and co-amoxicillin (9%, n = 4). In 19% of the protocols (n = 8), there was no distinction between mild or severe allergy to penicillin derivatives. In this group (n = 8), 75% (n = 6) administered clindamycin as the second choice, with 50% (n = 3 of 6) offering vancomycin as an alternative in cases of known clindamycin resistance or allergy. In the group with allergy severity classification (n = 35), first- and second-generation cephalosporins were preferred for mild penicillin allergy: 71% (n = 25) used cefazolin, 26% (n = 9) used cefuroxime and erythromycin was mentioned by n = 1. In 21 of the 33 received protocols with references, Expert Letter No. 19 from the Swiss Society of Gynaecology and Obstetrics (SGGG) was referenced, making up 64 % of the used literature. This was followed by other literature (58 %, n = 19) and the revised guidelines of the Swiss Society of Neonatology in collaboration with the Paediatric Infectious Disease Group Switzerland (PIGS) (30 %, n = 10). Mostly gynaecologists (90%; n = 28 of 31) were involved as authors of internal protocols. Neonatologists were not mentioned by any. CONCLUSION: Our study highlights that the management of intrapartum antibiotic prophylaxis is heterogeneous, and antimicrobial stewardship is lacking in most Swiss obstetric wards. In terms of literature, German-speaking wards in Switzerland are more orientated towards German-speaking neighbouring countries than French- and Italian-speaking wards. There is a need to enhance interdisciplinarity in the development of internal protocols and to create a joint national guideline among professional societies.